« On ne devrait exiger de personne de parler dans un micro ». Les débats autour de la présence des micros dans les prétoires dans la RFA des années 1950 - Nathalie Le Bouëdec (Criminocorpus)
In the Federal Republic of Germany, the 1964 law banning the recording and broadcasting of court hearings was preceded by more than a decade of debate, initially centred on the presence of microphones in courtrooms before the rise of television in the late 1950s. This paper analyses those discussions based on court archives documents, which shed light on both the discourses of the stakeholders and the practices adopted in the courts. The debates should also be seen in the context of new challenges facing the judicial institution, including the democracy-building process, while many of the judicial stakeholders remained the same as before 1945. The analysis shows that radio succeeded in carving out a – fragile – place for itself in West German courts. A critical discourse denouncing the presence of microphones as illegitimate and dangerous coexisted with a more open discourse, albeit in a minority. However, the position of the judiciary gradually hardened and, from 1959 onwards, against the backdrop of increasing tension between the judiciary and the media, there was a massive demand for a general ban on recordings.